Study of degradation of cellulose-acetate membrane in osmotic technique for bentonite soil characterisation - Muhammad Afiq, Mohd Tadza (2018)
Bentonite clays are promising materials for disposal of high-level nuclear waste (HLW). Malaysia has recently discovered bentonite could therefore potentially be useful in managing the nation’s HLW should Malaysia decide to embark on a nuclear power programme. This report presents comprehensive data on physical, chemical, mineralogical and microbiological information on the local bentonite. The soil-water retention curve (SWRC) study was conducted to elucidate characteristic soil-water interactions and to obtain further knowledge and understanding of the bentonite engineering properties and behaviour. In order to enable a wide range of suction on the soil sample, the above study was conducted by utilising the vapour equilibrium technique (VET) as well as the osmotic technique. However, since the cellulose acetate semipermeable membrane tends to degrade during testing, resulting in the intrusion of polyethylene glycol (PEG) molecules into the soil sample, there was a concern that the accuracy of the SWRC readings could be jeopardised. The presence of cellulase enzymes on the degraded membranes led to the suspicion that the degradation could have been caused by the fungi Trichoderma atroviridae and Paecilomyces lilacinus, which are found in soil. To confirm the suspicion, two antifungal agents namely chloroxylenol and iodine, were tested to eliminate the fungi. To test the efficacy of the antifungal agents, concentrations of 1 % to 20 % in 100 μl of PEG solution were used during fungal plating to determine the Minimum Inhibitory Concentration (MIC). The MIC test results showed that 8 % concentration of iodine was able to eliminate all traces of fungi whilst chloroxylenol was effective at 10 % concentration. The osmotic technique conducted in the presence of iodine showed no signs of intrusion but for chloroxylenol, there was still indication of intrusion. Field Emission Scanning Electron Microscopy (FESEM) confirmed the presence of fungus on untreated membrane samples as well as evidence of defects and tunneling. Screening by atomic-force microscopy (AFM) revealed evidence of degradation or enlarged pore sizes for the chloroxylenol-treated membranes. This was believed to be due to the abrasive chlorine component of chloroxylenol, thus creating possibility of PEG intrusion into the soil sample. As for the iodine-treated membranes, although there was pore size enlargement, it was not sufficient for the intrusion of PEG.